1995
DOI: 10.1111/j.1439-0434.1995.tb04554.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cross‐Reactive Antibodies to Detect Members of the Potyviridae

Abstract: ln attempts to use cross-reacting antibodies for the broad-spectrum detection of potyviruses, two broad-spectrum immunoreagents, the monoclonal antibody P-.^-3H8 and antiserum TuMV-3I4raised against an isolate of peanut stripe virus and turnip mosaic virus, respectively, were examined for their ability to detect members of the Polyriridae in a simple indirect plate-trapped antigen (PTA) ELISA. Both immunoreagents reacted strongly not only wilh isolates of 50 different virus species of the genus Posyrirux but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…To rule out the possibility that an aphid-borne potyvirus was contaminating the CVYV cultures, three series of experiments were conducted. CVYV-infected cucumber and melon plant extracts were tested in double-antibody sandwich (DAS)-ELISA with antisera raised against the five most common potyviruses encountered in cucurbits in the Mediterranean region (Lecoq et al, 1998) In addition, CVYV-infected plant extracts did not react in antigen-trapped indirect ELISA with monoclonal antibody PTY 1, which detects most aphid-transmitted potyviruses but which does not detect potyvirids transmitted by other vectors with the exception of Ryegrass mosaic virus (RGMV) (Jordan, 1992 ;Richter et al, 1995) (data not shown). Finally, attempts to transmit CVYV-Isr and CVYV-Jor by the aphid Myzus persicae by the non-persistent mode were unsuccessful (data not shown).…”
Section: Cucumber Vein Yellowing Virus (Cvyv) Is Widespread In Cucurbmentioning
confidence: 99%
“…To rule out the possibility that an aphid-borne potyvirus was contaminating the CVYV cultures, three series of experiments were conducted. CVYV-infected cucumber and melon plant extracts were tested in double-antibody sandwich (DAS)-ELISA with antisera raised against the five most common potyviruses encountered in cucurbits in the Mediterranean region (Lecoq et al, 1998) In addition, CVYV-infected plant extracts did not react in antigen-trapped indirect ELISA with monoclonal antibody PTY 1, which detects most aphid-transmitted potyviruses but which does not detect potyvirids transmitted by other vectors with the exception of Ryegrass mosaic virus (RGMV) (Jordan, 1992 ;Richter et al, 1995) (data not shown). Finally, attempts to transmit CVYV-Isr and CVYV-Jor by the aphid Myzus persicae by the non-persistent mode were unsuccessful (data not shown).…”
Section: Cucumber Vein Yellowing Virus (Cvyv) Is Widespread In Cucurbmentioning
confidence: 99%
“…data) and recently published 3' sequence information from a Danish isolate of RgMV, suggest that mite-transmitted RgMV is more closely related to viruses of the aphid-transmitted potyvirus genus (Schubert et al 1995). This assertion is supported by the serological reaction of RgMV to a number of general potyvirus antisera including PTY1 (Richter et al 1995). PTY1 reacts with mostpotyviruses, but with the exception of RgMV, does not react with rymo-, bymo-, or ipomoviruses (Richter et al 1995).…”
Section: Introductionmentioning
confidence: 88%
“…This assertion is supported by the serological reaction of RgMV to a number of general potyvirus antisera including PTY1 (Richter et al 1995). PTY1 reacts with mostpotyviruses, but with the exception of RgMV, does not react with rymo-, bymo-, or ipomoviruses (Richter et al 1995).…”
Section: Introductionmentioning
confidence: 91%
“…First, we attempted to purify virus particles from infected plants for use as immunogens and we then screened for MAbs that recognized several potyviruses, similar to previous reports of MAbs prepared against Johnsongrass mosaic virus (JGMV) (42), Tulip breaking virus (43), TEV (44,45), and Peanut stripe virus (PStV) (46). Unfortunately, it was difficult to purify enough virus particles from calla lily to produce high-quality antiserum or antibody for detection, most likely due to the mucilage in the plant tissues (17,47).…”
Section: Discussionmentioning
confidence: 99%